TOKSISITAS AKUT SERBUK CACING TANAH (Pheretima javanica K.) KERING MELALUI PENGAMATAN FAAL GINJAL TIKUS PUTIH (Rattus norvegicus) - Anggun Rifka Rozi; Joko Waluyo; Jekti Prihatin (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2017)
Abstract: Utilization of earthworms (Pheretima javanica K.) other than as a soil fertilizing organism is an alternative treatment for typhoid fever as a traditional medicine and provided in the form of whole powder. This study was conducted to determine the toxicity effects of earthworm powder on kidneys in white rats (Rattus norvegicus). Total of 50 white rats were divided into five groups consisting of negative control (2 ml CMC Na 1%), group P1 0,4 grams, group P2 0,8 grams, P3 group 1.6 grams, and P4 group 3.2 grams of dry earthworm powder. White mice were then acclimated for approximately one week and induced with dry earthworm powder orally. The study was conducted for 14 days to see the description of the toxic effects caused. The results of data analysis using ANOVA showed that each dose of dry earthworm powder had no effect on kidney function of white rats (Rattus norvegicus). Keywords: Pheretima javanica K.; Rattus norvegicus; kidney function